(NiZBRANNOE(B: (NnAUKA O KULXTURE (B/s - (NuAJT(B, (NlESLIs ((NmOSKWA (B:s (Nrossp|n(B,s, 2004)
(Nw RABOTAH PREDSTAWLEN RQD ORIGINALXNYH AWTORSKIH KONCEPCIJ(B: (NKONCEPCIQ \WOL@CII KULXTURY(B, (NOPIRA@]AQSQ NA \NERGETI^ESKU@ TEORI@ uAJTA(B; (NOBOSNOWANIE KONCEPCII NAUKI O KULXTURE(B, (NKULXTUROLOGII(B, (NI OBOZNA^ENIE EE MESTA W SISTEME NAUK (BXX (NW(B.s
Keywords: (NsOCIOLOGIQ KULXTURY I CIWILIZACIIs